THE POLITICAL ECONOMY OF BOLSONARO’S GOVERNMENT (2019-2022) AND LULA DA SILVA’S THIRD TERM (2023-2026) - Ferrari Filho, Fernando; Bittes Terra, Fábio Henrique (Investigación Económica, 2023)
The article has two objectives: First, it analyses the economic policy of the Jair Bolsonaro government (2019-2022), which we define as ‘dispersed’ and ‘reactive’; second, it presents the economic challenges that Luiz Inácio Lula da Silva will face in his third term. We also speculate about proposals for possible economic policy that the Lula da Silva government should implement. LA ECONOMÍA POLÍTICA DEL GOBIERNO BOLSONARO (2019-2022) Y DE LA TERCERA PRESIDENCIA DE LULA DA SILVA (2023-2026) RESUMEN El artículo tiene dos objetivos: primero, analiza la política económica del gobierno de Jair Bolsonaro (2019-2022), que definimos como ‘dispersa’ y ‘reactiva’. El segundo es presentar los desafíos económicos que encontrará Luiz Inácio Lula da Silva en su tercer mandato. También especulamos sobre propuestas de posibles políticas económicas que deberá implementar el gobierno de Lula da Silva.